Nutritional status of school children living in Northern part of Sri Lanka - M. G. Sathiadas; Annieston Antonyraja; Arunath Viswalingam; Kasthuri Thangaraja; V. P. Wickramasinghe (BMC, 2021)
Abstract Background Nutritional status is an important indicator for measuring quality of life in children. A region that is recovering from war will face many problems related to nutrition. Very few studies have addressed the nutritional problems in school children. This study was undertaken to identify the prevalence of wasting, stunting and obesity among school children from Northern Sri Lanka and associated socio-demographic factors. Methods A community based cross-sectional study was carried out using multistage stratified proportionate cluster among healthy children attending schools in the Northern part of the country. Height and weight were measured, and Body Mass Index (BMI) calculated [weight (kg)/Height (m) 2]. BMI-for-age z-score (BAZ) and Height for age Z (HAZ) scores were determined and WHO growth references were used to categorise the nutritional status. Correlation between various nutritional problems with Maternal education, household income, number of family members and the residential area was assessed. Results A total of 1012 children were recruited, and the mean age and standard deviation were 11.12±1.77 yrs. Girls in the age ranges of 9-14 were heavier and taller when compared to the boys compatible with the pubertal growth spurt. Stunting based on the height for age was seen in 10.9% of boys and 11.8% of girls. Wasting based on BMI for age WHO standard (WHO 2007) was seen in 30.6% of boys and 29.1% of the girls. The prevalence of overweight was 11% and Obesity was 6.3% of the population. Obesity was predominantly seen in boys (4.2%) and it was significantly higher when compared to the girls (2.1%) (p < 0.001). Obesity in older boys (> 10 years) was significantly more than the younger ones (p < 0.01). Maternal education and family income had a significant impact on the prevalence of wasting, stunting and obesity whereas the family size contributed to the wasting and obesity (p< 0.001). Conclusion Findings suggest that stunting, wasting, overweight and obesity are prevalent among 6-16-year-old leading to concerns in public health. The nutritional status significantly varies according to the geographical location, maternal education and the household income.